Relating physicochemical and microbiological safety indicators during processing of linguiça, a Portuguese traditional dry-fermented sausage. (December 2015) - Gonzales-Barron, U.; Cadavez, V.; Pereira, A.P.; Gomes, A.; Araújo, J.P.; Saavedra, M.J.; Estevinho, L.; Butler, F.; Pires, P.; Dias, T.
Abstract: Linguiça is a Portuguese traditional fermented sausage whose microbiological quality and safety can be highly variable. In order to elucidate risk factors and the particularities of the manufacturing technology that explain the between-batch variability in total viable counts (TVC), Enterobacteriaceae, Staphylococcus aureus and Listeria monocytogenes in the product; microbiological and physicochemical characterisation of linguiça at five stages of production (i.e., raw pork meat, mixed with ingredients, macerated, smoked and ripened) was carried out. A total of six production batches were surveyed from two factories; one utilised curing salts and polyphosphate in their formulation (Factory II). The delayed fermentation in the nitrite-formulated sausages was partly responsible for the increase (p < 0.01) in Enterobacteriaceae, S. aureus and L. monocytogenes from raw meat (3.21 log CFU/g, 1.30 log CFU/g and 22.2 CFU/g, respectively) to the end of maceration (4.14 log CFU/g, 2.10 log CFU/g and 140 CFU/g, respectively) while the better acidification process in the nitrite-free sausages (Factory I) led to lower counts of S. aureus (2.64 log CFU/g) and L. monocytogenes (10 CFU/g) in the finished products. In Factory II, although L. monocytogenes entered the chain at the point of mixing, it became steadily inactivated during smoking and ripening (< 50 CFU/g), despite the initially-delayed fermentation. Nitrite had a strong effect on reducing Enterobacteriaceae throughout smoking (r = − 0.73) and ripening (r = − 0.59), while it failed to control the growth of S. aureus . The main hurdle preventing the development of S. aureus in linguiça is the pH, and other factors contributing to its control are: longer ripening days (p = 0.019), low S. aureus in raw meat (p = 0.098), properly-washed casings (p = 0.094), and less contamination during mixing (p = 0.199). In the case of L. monocytogenes, at least three hurdles hinder its development in linguiça : low aw (p = 0.004), low pH (p = 0.040) and nitrite (p = 0.060), and other factors contributing to its control are: longer ripening (p = 0.072) and maceration (p = 0.106) periods, lower aw at the end of smoking (p = 0.076) and properly-washed casings (p = 0.099). Results have shown that there is a need to standardise the productive process of linguiça, to optimise the initial acidification process, and to reinforce proper programmes of quality control of ingredients and good hygiene practices, so as to minimise the introduction of Enterobacteriaceae and pathogens from external sources. Highlights: Mixing is a critical stage as Enterobacteriaceae and pathogens increased significantly. Nitrite contributed to the decrease in Enterobacteriaceae and L. monocytogenes . In batches with poor acidification process, S. aureus increased steadily after maceration. Contaminated casings influenced the final counts of Enterobacteriaceae and pathogens. Long duration batches led to lower L. monocytogenes counts in final product.